2007
DOI: 10.1073/pnas.0610362104
|View full text |Cite
|
Sign up to set email alerts
|

Childhood maltreatment predicts adult inflammation in a life-course study

Abstract: Stress in early life has been associated with insufficient glucocorticoid signaling in adulthood, possibly affecting inflammation processes. Childhood maltreatment has been linked to increased risk of adult disease with potential inflammatory origin. However, the impact of early life stress on adult inflammation is not known in humans. We tested the life-course association between childhood maltreatment and adult inflammation in a birth cohort followed to age 32 years as part of the Dunedin Multidisciplinary H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

52
790
4
15

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 1,071 publications
(879 citation statements)
references
References 44 publications
52
790
4
15
Order By: Relevance
“…Recently, Danese et al (2007) found childhood maltreatment to predict elevated adult CRP levels independently of adult circumstances. The Whitehall II study does not have a measure of childhood maltreatment, but father's social class as a marker of early life circumstances has been shown to be inversely associated with adult fibrinogen levels in these data.…”
Section: Inflammation As a Predictor Of Depressive Symptomsmentioning
confidence: 99%
“…Recently, Danese et al (2007) found childhood maltreatment to predict elevated adult CRP levels independently of adult circumstances. The Whitehall II study does not have a measure of childhood maltreatment, but father's social class as a marker of early life circumstances has been shown to be inversely associated with adult fibrinogen levels in these data.…”
Section: Inflammation As a Predictor Of Depressive Symptomsmentioning
confidence: 99%
“…41 DNA-methylation has been shown to persist from early developmental stages into adulthood 25 and thus is the most likely candidate mechanism for persistent memory trace between childhood experiences and adult depression. Epigenetic modifications resulting from adverse childhood experiences are likely to modify through the life course the expression and inducibility by stress of key proteins in the hypothalamus-pituitaryadrenal axis, 24,25 neurotrophins, 42 immune system 43 and serotonergic neurotransmission, 44,45 and thus shape the vulnerability to depression.…”
Section: Principles Of Gene-environment Interactionsmentioning
confidence: 99%
“…Kiecolt-Glaser et al, 2002Danese et al, 2007]. It also impairs wound healing, and increases the severity and prevalence of noninfectious pathologies (e.g.…”
Section: Increased Morbidity and Decreased Lifespanmentioning
confidence: 99%